Reduced expression of argininosuccinate synthetase 1 has a negative prognostic impact in patients with pancreatic ductal adenocarcinoma. - Qingqing Liu; John Stewart; Hua Wang; Asif Rashid; Jun Zhao; Matthew H Katz; Jeffrey E Lee; Jason B Fleming; Anirban Maitra; Robert A Wolff; Gauri R Varadhachary; Sunil Krishnan; et al. (PLoS ONE)
Argininosuccinate synthetase 1 (ASS1), the rate-limiting enzyme for arginine biosynthesis, is expressed in many types of human malignancies. Recent studies showed that ASS1 may have tumor suppressor function and that ASS1 deficiency is associated with clinical aggressiveness in nasopharyngeal carcinoma, myxofibrosarcomas and bladder cancer. The goal of this study was to evaluate the prognostic impact of ASS1 expression in patients with pancreatic ductal adenocarcinoma (PDAC). Our study included two independent cohorts: untreated cohort, which was comprised of 135 patients with PDAC who underwent pancreatoduodenectomy (PD) without pre-operative neoadjuvant therapy, and treated cohort, which was comprised of 122 patients with PDAC who have completed neoadjuvant therapy and PD. The expression level of ASS1 was evaluated by immunohistochemistry and the results were correlated with clinicopathologic parameters and survival using SPSS statistics. Our study showed that 12% of PDAC in untreated cohort and 15% of PDAC in treated cohort has low expression of ASS1 (ASS1-low). ASS1-low was associated with higher recurrence (p = 0.045), shorter disease-free survival (DFS, 4.8 ± 1.6 months vs 15.3 ± 2.2 months, p = 0.001) and shorter overall survival (OS, 14.6 ± 6.4 months vs 26.5 ± 3.5 months, p = 0.005) in untreated cohort and shorter OS in treated cohort compared to ASS1-high tumors. In multivariate analysis, ASS1-low (HR: 0.45, 95% CI: 0.26-0.79, p = 0.005) was an independent prognostic factor for DFS in untreated cohort and an independent prognostic factor for OS (HR: 0.56, 95% CI: 0.32-0.97, p = 0.04) in treated cohort. Our results provide supporting evidence for future clinical trial using arginine deprivation agents either alone or in combination with conventional chemotherapy in treating pancreatic cancer.